(untitled) (Journal of Statistical Research, 2023)
Divergence between two distributions has been of statistical interest for more than a century, beginning with Karl Pearson with his famous chisquare test. The paper revisits some of the well-known density divergence measures, and studies their interrelationship. In addition, it is demonstrated how Scheffe’s pointwise density convergence implies convergence of distributions, based on different divergence measures. Journal of Statistical Research 2022, Vol. 56, No. 1, pp. 1-10